Some physiological and biochemical changes in women with hyperthyroidism - Sarab D. Kh. (Tikrit Journal of Pure Science)
Physiological changes, have been described in hyperthyroidism. There is interaction among hypothalamus gland, pituitary gland and thyroid gland system in regulation of metabolic and function of body, this achieved by balance between hormonal stimulation with drawl of other hormone by feed back mechanism, any changes in this hormonal balance lead to thyroid gland disorders , the present study was carried out to evaluate the effect of hyperthyroidism on some physiological blood properties is Hb, WBC, RBC, blood pressure, determination the concentration of thyroid hormones (T3, T4, TSH) for patients (N=50) which compared with control group (N=50). The following finding were obtained :